The Effect of Handling Complaint and Hospital Service Quality on Patient Satisfaction and Loyalty - Siti Fatonah; Heny Palupi (Universitas Muhammadiyah Yogyakarta, 2020)
The aim of this research is to investigate the effect of handling complaints and hospital service quality on patient satisfaction and patient loyalty. The sample of this study was patients at hospitals in the Sragen Regency, Central Java. This study used a quantitative research design to test the hypothesis research model. The total sample in this study was 90 patients and it used random sampling as the technique sample. Path analysis was used to test the research model. The results of this study show that there are positive significant effects between handling complaints and patient satisfaction. Second, there are positive significant effects between hospital service quality and patient satisfaction. Finally, there are positive significant effects between patient satisfaction and patient loyalty.